SISTEM PAKAR DIAGNOSA PENYAKIT MENULAR PADA BALITA DENGAN METODE BAYES - Romanus Damanik (UNIVERSITAS PELITA HARAPAN, 2018)
ABSTRACTInfectious diseases known as infectious diseases are a disease caused by a biological agent (such as viruses, bacteria or parasites), which can be transmitted or transmitted to others through certain media such as air, food and drink that are less clean , syringes and blood transfusions and direct contact with the patient. The expert system is one of the branches of Artificial Intelligence that makes extensive use of knowledge, especially for the expert-level problem-solving. Bayes is a simple probabilistic based prediction technique based on bayes rules. The goal to be achieved is to create a useful expert system application as a tool to get information on infectious diseases in infants.